Whole genome sequencing–based copy number variations reveal novel pathways and targets in Alzheimer's disease. Issue 10 (17th December 2021) - Ming, Chen; Wang, Minghui; Wang, Qian; Neff, Ryan; Wang, Erming; Shen, Qi; Reddy, Joseph S.; Wang, Xue; Allen, Mariet; Ertekin‐Taner, Nilüfer; De Jager, Philip L.; Bennett, David A.; et al.
Abstract: Introduction: A few copy number variations (CNVs) have been reported for Alzheimer's disease (AD). However, there is a lack of a systematic investigation of CNVs in AD based on whole genome sequencing (WGS) data. Methods: We used four methods to identify consensus CNVs from the WGS data of 1, 411 individuals and further investigated their functional roles in AD using the matched transcriptomic and clinicopathological data. Results: We identified 3, 012 rare AD‐specific CNVs whose residing genes are enriched for cellular glucuronidation and neuron projection pathways. Genes whose mRNA expressions are significantly correlated with common CNVs are involved in major histocompatibility complex class II receptor activity. Integration of CNVs, gene expression, and clinical and pathological traits further pinpoints a key CNV that potentially regulates immune response in AD. Discussion: We identify CNVs as potential genetic regulators of immune response in AD. The identified CNVs and their downstream gene networks reveal novel pathways and targets for AD.